Long term prognosis of recurrent haematuria. Issue 5 (May 1985) - Miller, P F; Speirs, N I; Aparicio, S R; Lendon, M; Savage, J M; Postlethwaite, R J; Brocklebank, J T; Houston, I B; Meadow, S R
Abstract : A long term follow up study of 100 children referred with recurrent haematuria for at least one year to two regional paediatric nephrology units is described. The mean duration of follow up was 8.2 years. An adequate renal biopsy was obtained in 96 and eight cases of Alport's syndrome and 10 of IgA nephropathy were diagnosed (20% and 26% respectively of the biopsies examined by electron microscopy and immunofluorescence). Five patients developed end stage renal failure and six hypertension requiring treatment, with the occurrence of these complications increasing progressively with increasing duration of follow up (1% at five years compared with 12% at 10 years). Adverse prognostic features were persistence of microscopic haematuria, proteinuria at presentation, and appreciable changes on renal biopsy. Eighty four patients had first degree relatives tested for haematuria; 30% of these families had another affected member. With long term follow up recurrent haematuria is associated with considerable morbidity and potential mortality.